Effect of Boiled Water Tithonia diversifolia A. Gray Leaf Against the Pancreas Histology in Mus musculus L. Induced by Alloxan - Yenni Fitri; Elsa Yuniarti (UNIVERSITAS NEGERI PADANG, 2019)
Traditional medicine is one of the drugs used by the community to be one of the efforts to treat diseases. One of them is Diabetes Mellitus (DM). DM is a metabolic disease characterized by hyperglycemia which results in an increase in free radicals in the cell. DM treatment is quite expensive so an alternative drug is needed. One of them is Tithonia diversifolia A. Gray. This study used a completely randomized design, consisting of 1 control, 4 treatments (P1: Only alloxan induced), P2: Alloxan 65 mg / kg BB, P3: Metformin 65 mg / kg BB, P4: Boiled leaves of moon leaves 24.6 mg / 10 ml and P4: Moon flower leaves boiled water 49.1 mg / 10 ml. The parameters observed were blood sugar in male mice and the number of cells in the islands of Langerhans before and after being given boiled leaves of moon flowers and metformin. Data were analyzed using ANOVA then continued with DMRT test with a significant difference of 5%. The results showed that administration of boiled kembang bulan leaves and metformin for 7 days could reduce blood sugar levels in mice and accelerate the regeneration of pancreatic cells. The most significant impact is the treatment with the highest dose, namely P4 (Moon leaf leaves boiled water 49.1 mg / 10 ml).